2021
DOI: 10.1158/1055-9965.epi-20-1555
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Polluted Neighborhoods and TP53-Mutated Non–Small Cell Lung Cancer

Abstract: Background: Poor patients often reside in neighborhoods of lower socioeconomic status (SES) with high levels of airborne pollutants. They also have higher mortality from non–small cell lung cancer (NSCLC) than those living in wealthier communities. We investigated whether living in polluted neighborhoods is associated with somatic mutations linked with lower survival rates, i.e., TP53 mutations. Methods: In a retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Patients who lived in highly-polluted regions had three times higher mutated genes, including TP53 , as those in control, lower-pollution regions. Our previous work found that TP53 -mutated NSCLC was linked to areas with higher PM 2.5 exposure [ 27 ]. However, this work only focused on TP53 -mutated NSCLC and on two pollutants (PM 2.5 and ozone), which were assessed through EPA’s EJScreen in the year or two prior to cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who lived in highly-polluted regions had three times higher mutated genes, including TP53 , as those in control, lower-pollution regions. Our previous work found that TP53 -mutated NSCLC was linked to areas with higher PM 2.5 exposure [ 27 ]. However, this work only focused on TP53 -mutated NSCLC and on two pollutants (PM 2.5 and ozone), which were assessed through EPA’s EJScreen in the year or two prior to cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study among patients who were treated at City of Hope Comprehensive Cancer Center (COH) in California (CA), patients living in areas with higher PM 2.5 exposure had 1.66 (95% CI: 1.02–2.72) increased odds of TP53 -mutated non-small cell lung cancer (NSCLC) [ 27 ]. That study measured air pollution (PM 2.5 and ozone) with the EPA’s Environmental Justice Screening and Mapping Tool (EJScreen).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have suggested a link between PM 2.5 exposure and increased aggressive biology [51], lung cancer risk and mortality in smokers [52] and never smokers [53]. The literature has also revealed that predominantly Black communities have higher exposure to air pollution, despite producing less of it [54].…”
Section: Air Pollutionmentioning
confidence: 99%
“…The United States Environmental Protection Agency's Environmental Justice Screening and Mapping Tool (EJSCREEN) provides a consistent and standardized approach to combining both environmental and demographic indicators by census block across States (EPA, 2021). Common neighborhood‐level structural and social risk exposures measured across studies include a higher proportion of minority populations (Erhunmwunsee et al., 2021), a higher frequency of the population with less than a high school education (Erhunmwunsee et al., 2021), and low socio‐economic status and increased proximity to industrial or facility location (Cifuentes et al., 2019).…”
Section: Measurement Of Sdoh Factors In Research and Clinical Settingsmentioning
confidence: 99%
“…The EJSCREEN tool can be used to indicate associations between the built environment and community exposures to SDOH factors with many adverse health outcomes, such as non‐small cell lung cancer and pregnancy complications (Cifuentes et al., 2019; Erhunmwunsee et al., 2021). A study of the Public Health Exposome in an African‐American Women's cohort in Ohio demonstrated that pregnant women reporting low income were more likely to live in areas with lower air quality, and/or closer to risk management facilities and/or direct discharges in water; all exposures were associated with increased risk of preterm birth and low birth weight (Cifuentes et al., 2019).…”
Section: Health Outcomes Associated With Sdoh Exposuresmentioning
confidence: 99%